Urban areas as landscapes of contemporary historical cities in Peru - De Orellana Rojas, Juan (2013)
Since the emergence of the first urban settlements began, intuitively, the formation and use of urbanspaces. At first there was no rationalization or reflection of them and its social importance, but were merely remnants between one building and another. In some cases, there was even a concept of street. The accommodation was spontaneous and additive. When these settlements developed and, in parallel, society slowly changed into a surplus economy, there was need for social meeting places and exchange dealer. The separation of groups of buildings led to the “width” of streets, which then were becoming more regular spaces, which resulted in the squares. The plaza are very old in the cities of the West, but the plazas as we know them today are of the modern age and its design has a clear and strong influence of large pre-Columbian American cultures. It will end with a case study